Objective structured clinical examination (OSCE): níveis de estresse, ansiedade e percepções de estudantes de medicina relacionados ao desempenho – um estudo de métodos mistos - Rodrigues, Maria Cláudia Cândida (2021)
Introduction: The Objective Structured Clinical Examination (OSCE) is recognized worldwide as a valid and efficient instrument to assess cognitive, psychomotor and communication skills in healthcare. However, increased levels of stress and anxiety are often reported by students at the time of their performance. Thus, the objective of this research was to assess the existence of an association between the level of anxiety and perceived stress and performance on the OSCE, as well as to understand the student's perception of the test and factors related to their performance. Method: A mixed, cross-sectional study with sequential explanatory design was carried out. In the quantitative approach, self-administered daytime sleepiness, anxiety and stress questionnaires were used for 213 students from the medical internship, immediately before taking the OSCE. Multiple linear regression, by the hierarchical method, was used to verify the independent variables associated with the performance. For data collection from the qualitative approach, the focus group method (FG) was used, with subsequent use of the IRAMUTEQ software to assist in the processing of data which were analyzed using Minayo's thematic analysis. Results: The variables gender, course term, daytime sleepiness, anxiety, and stress did not influence the students' performance in the OSCE. The thematic saturation process was achieved with five focus groups, with the total participation of 38 students. Four core classes emerged from the narratives: “Meanings of OSCE for the student”; “Feelings related to OSCE performance”; “Operational factors related to performance in the OSCE”; and “Challenges related to competences (not) assessed by the OSCE”. Conclusion: Academic performance in the OSCE was not influenced by the stress and anxiety perceived by students during its performance. The OSCE is perceived by students as a purely summative assessment tool, associated with negative emotions, with stress and the evaluator's posture perceived as preponderant factors in the performance of students within the evaluative framework.